1967
DOI: 10.1093/jaoac/50.6.1216
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Carbon Adsorbents and Quantitative Elution and Separation of Forty-two Pesticides from a Carbon-Solka Floe Cleanup Column

Abstract: Ten different carbons were investigated as adsorbents in a column cleanup procedure for extracts of lettuce and carrots. Organochlorine pesticides were eluted with 175 nil of 1.5% acetonitrile in hexane. The quantitative elution of 13 pesticides as a mixture with and without the presence of carrot or lettuce extract was determined by gas-liquid chromatography (GLC) with electron capture detection (ECD). The mean recovery values for each pesticide from all carbons, excluding Norit A neutral, ranged from 87 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1969
1969
1990
1990

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Samuel [56] utilizou o carvão activado misturado com óxido de alumínio, celite, sulfato de sódio e attapulgus clay para purificar diferentes tipos de extractos. Embora Mukherjee e colaboradores [50] ao efectuarem o estudo da eficiência de várias colunas com diferentes adsorventes tenham verificado que o carvão activo se mostrou mais eficaz na remoção de pigmentos e gorduras, McLeod e colaboradores [44] ao estudarem dez tipos diferentes de carvão verificaram que a sua capacidade de retenção para ceras e óleos não era tão elevada quanto para os pigmentos. Adachi e colaboradores [1] estabeleceram um método para a análise de amostras de leite procedendo à purificação com 0,5 g de carvão activado contido em minicolunas de 15 mm de d.i.…”
Section: Carvãounclassified
“…Samuel [56] utilizou o carvão activado misturado com óxido de alumínio, celite, sulfato de sódio e attapulgus clay para purificar diferentes tipos de extractos. Embora Mukherjee e colaboradores [50] ao efectuarem o estudo da eficiência de várias colunas com diferentes adsorventes tenham verificado que o carvão activo se mostrou mais eficaz na remoção de pigmentos e gorduras, McLeod e colaboradores [44] ao estudarem dez tipos diferentes de carvão verificaram que a sua capacidade de retenção para ceras e óleos não era tão elevada quanto para os pigmentos. Adachi e colaboradores [1] estabeleceram um método para a análise de amostras de leite procedendo à purificação com 0,5 g de carvão activado contido em minicolunas de 15 mm de d.i.…”
Section: Carvãounclassified
“…Activated carbon, the age-old purifier, continues to offer expanded applications in the treatment of municipal and industrial wastes, in the recovery and purification of synthetic and natural substances, and in numerous other chemical and environmental processes (1)(2)(3). New applications of activated carbons in the separation and purification of organic compounds are largely the result of the availability of more sophisticated preparations of activated carbons possessing more refined chemical and physical properties (3)(4)(5)(6)(7). Research at the Columbia National Fisheries Research Laboratory has shown that the application of the uniquely selective adsorptive properties of certain activated carbons to the purification of organic compounds can be seriously limited by the development of high back-pressure in chromatography columns packed with finely divided carbon and by poor recoveries of strongly absorbed substances, even from sub-gram quantities of carbon.…”
mentioning
confidence: 99%
“…McLeod and cow-orkers (151) Watts and Storherr {229) continued their studies of the sweep codistillation cleanup procedure. They described a cleanup of milk solvent extract for the determination of organophosphate and chlorinated hydrocarbon pesticides.…”
mentioning
confidence: 99%